The daily rhythms of mitochondrial gene expression and oxidative stress regulation are altered by aging in the mouse liver. (21st October 2015) - Gong, Changxia; Li, Chengwei; Qi, Xiaoqing; Song, Zhiyin; Wu, Jianguo; Hughes, Michael E.; Li, Xiaodong
Abstract : The circadian clock regulates many cellular processes, notably including the cell cycle, metabolism and aging. Mitochondria play essential roles in metabolism and are the major sites of reactive oxygen species (ROS) production in the cell. The clock regulates mitochondrial functions by driving daily changes in NAD + levels and Sirt3 activity. In addition to this central route, in the present study, we find that the expression of some mitochondrial genes is also rhythmic in the liver, and that there rhythms are disrupted by the Clock Δ19 mutation in young mice, suggesting that they are regulated by the core circadian oscillator. Related to this observation, we also find that the regulation of oxidative stress is rhythmic in the liver. Since mitochondria and ROS play important roles in aging, and mitochondrial functions are also disturbed by aging, these related observations prompt the compelling hypothesis that circadian oscillators influence aging by regulating ROS in mitochondria. During aging, the expression rhythms of some mitochondrial genes were altered in the liver and the temporal regulation over the dynamics of mitochondrial oxidative stress was disrupted. However, the expression of clock genes was not affected. Our results suggested that mitochondrial functions are combinatorially regulated by the clock and other age-dependent mechanism(s), and that aging disrupts mitochondrial rhythms through mechanisms downstream of the clock.